MicroRNA-668-3p inhibits myoblast proliferation and differentiation by targeting Appl1 - Haigang Cao; Tianning Du; Chenchen Li; Lingling Wu; Jieming Liu; Yuan Guo; Xiao Li; Gongshe Yang; Jianjun Jin; Xin’e Shi (BMC Genomics, 2023)
Abstract Background Skeletal muscle is the largest tissue in the body, and it affects motion, metabolism and homeostasis. Skeletal muscle development comprises myoblast proliferation, fusion and differentiation to form myotubes, which subsequently form mature muscle fibres. This process is strictly regulated by a series of molecular networks. Increasing evidence has shown that noncoding RNAs, especially microRNAs (miRNAs), play vital roles in regulating skeletal muscle growth. Here, we showed that miR-668-3p is highly expressed in skeletal muscle. Methods Proliferating and differentiated C2C12 cells were transfected with miR-668-3p mimics and/or inhibitor, and the mRNA and protein levels of its target gene were evaluated by RT‒qPCR and Western blotting analysis. The targeting of Appl1 by miR-668-3p was confirmed by dual luciferase assay. The interdependence of miR-668-3p and Appl1 was verified by cotransfection of C2C12 cells. Results Our data reveal that miR-668-3p can inhibit myoblast proliferation and myogenic differentiation. Phosphotyrosine interacting with PH domain and leucine zipper 1 (Appl1) is a target gene of miR-668-3p, and it can promote myoblast proliferation and differentiation by activating the p38 MAPK pathway. Furthermore, the inhibitory effect of miR-668-3p on myoblast cell proliferation and myogenic differentiation could be rescued by Appl1. Conclusion Our results indicate a new mechanism by which the miR-668-3p/Appl1/p38 MAPK pathway regulates skeletal muscle development.